Calcium Homeostasis in the Epididymal Microenvironment: Is Extracellular Calcium a Cofactor for Matrix Gla Protein-Dependent Scavenging Regulated by Vitamins - Shum, Winnie; Zhang, Bao Li; Cao, Albert Shang; Zhou, Xin; Shi, Su Meng; Zhang, Ze Yang; Gu, Lou Yi; Shi, Shuo (Frontiers in Cell and Developmental Biology, 2022)
In the male reproductive tract, the epididymis is an essential organ for sperm maturation, in which sperm cells acquire mobility and the ability to fertilize oocytes while being stored in a protective microenvironment. Epididymal function involves a specialized luminal microenvironment established by the epithelial cells of epididymal mucosa. Low-calcium concentration is a unique feature of this epididymal luminal microenvironment, its relevance and regulation are, however, incompletely understood. In the rat epididymis, the vitamin D-related calcium-dependent TRPV6-TMEM16A channel-coupler has been shown to be involved in fluid transport, and, in a spatially complementary manner, vitamin K2-related γ-glutamyl carboxylase (GGCX)-dependent carboxylation of matrix Gla protein (MGP) plays an essential role in promoting calcium-dependent protein aggregation. An SNP in the human GGCX gene has been associated with asthenozoospermia. In addition, bioinformatic analysis also suggests the involvement of a vitamin B6-axis in calcium-dependent MGP-mediated protein aggregation. These findings suggest that vitamins interact with calcium homeostasis in the epididymis to ensure proper sperm maturation and male fertility. This review article discusses the regulation mechanisms of calcium homeostasis in the epididymis, and the potential role of vitamin interactions on epididymal calcium homeostasis, especially the role of matrix calcium in the epididymal lumen as a cofactor for the carboxylated MGP-mediated scavenging function.